COMPARATIVE ANALYSIS OF TECHNICAL IDICATORS AND TACTICAL UTILITY OF THEIR APPLICATION IN FOOTBALL - Peko Vujović; Miroslav Radoman (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The aim of the research is to ascertain the manifested differences in the inner structure of the game and to establish and notify the tendencies of football game development movement by a comparative analysis, according to the manifested differences that examined according to the technical and tactics characteristics. The specimen is representative, thus the research includes the most successful national teams (semi-final and final) on XVI, XVII and XVIII World Football Championship. The analysis includes offensive playing, movements of certain players during the game, the way in which the ball is passed, the goalkeeper's performance... This research has once again proved the presence of permanent further tendencies of movement of the contemporary top-level football.